Historical archaeology of the Mapungubwe area: Boer, Birwa, Sotho-Tswana and Machete - Huffman, T. N. (Southern African Humanities, 2012)
In the Mapungubwe area, nineteenth-century Venda capitals housed virtually the entire chiefdom, totalling only some 350 people. This was in marked contrast to the earlier, and related, Khami period, largely because of different climatic conditions. Although sparsely populated, interaction of the Venda-speaking Machete chiefdom with Birwa and Sotho-Tswana created a heterogeneous social landscape. Before Machete moved to Leokwe Hill, Bambandyanalo was the Birwa capital under a Kalanga chief. In addition to ethnic interaction with Birwa and Sotho-Tswana, internal politics, the purchase of farms in the 1870s, the Anglo-Boer War and the search for diamonds affected the Machete chiefdom. When Mapungubwe was re-discovered in the early 1930s, the chiefdom had already disintegrated, and the people spoke Sotho.